PdII‐Mediated Oxidative Amination for Access to a 9‐Azabicyclo[4.2.1]nonane Compound Library and Anatoxin‐a. Issue 40 (18th October 2018) - Dawood, Rafid S.; Chidipudi, Suresh R.; O'Connor, Daniel C.; Lewis, William; Hamza, Daniel; Pearce, Christopher A.; Jones, Geraint; Wilkie, Ross P.; Georgiou, Irene; Storr, Thomas E.; Moore, Jonathan C.; Stockman, Robert A.
Abstract : Intramolecular oxidative amination of readily accessible aminocyclooct‐4‐enes provides rapid and regioselective access to the 9‐azabicyclo[4.2.1]nonane framework characteristic of the natural product anatoxin‐a (1). This has enabled the synthesis of sp 3 ‐rich chemical scaffolds suitable for diversification. A library of 881 lead‐like compounds is reported alongside a formal synthesis of anatoxin‐a (1). Abstract : Biologically relevant 9 azabicyclo[4.2.1]nonanes can be synthesised through an intramolecular oxidative amination of aminocyclooct‐4‐enes. The reaction is generally high yielding, has good substrate scope and proceeds under "ligand‐free" catalytic conditions. The protocol was applied to the synthesis of anatoxin‐a and a series of chemical scaffolds, which were further derivatised to form an 881‐membered compound library.